Review of the Genus Platystethus Mannerheim (Coleoptera: Staphylinidae: Oxytelinae) in China - Lü, Liang; Zhou, Hong-Zhang (Zootaxa, 2015)
Platystethus Mannerheim, currently comprising 53 species, is a widespread genus of the subfamily Oxytelinae in Northern Hemisphere. Platystethus species are most commonly found in dung and other decaying plant materials, occasionally on stream banks. In this paper, we reviewed all 12 species currently known from China. Three species are described as new to science: P. bucerus sp. nov. (from Xizang and Sichuan), P. subnitens sp. nov. (from Xinjiang), and P. vicinior sp. nov. (from Xinjiang). A synonymy is re-proposed: P. cornutus (Gravenhorst) = P. operosus Sharp. The lectotype is designated for P. operosus Sharp, 1874. All previously known Chinese species are redescribed and a key is provided to the species from China and adjacent regions. Diagnostic details of the treated taxa are illustrated by color photographs and by line drawings.